Nutilor (Moringa Leaf and Chicken Liver Nuggets) as Food for Stunting Prevention - Bertalina, Bertalina; Sirajudin, Sirajudin (Jurnal Kesehatan, 2024)
Providing complementary foods for breast milk (MP-ASI) is very important because the age of >6 months to 2 years, nutrients are needed to support children's growth and development during the golden period. Nuggets are a high-protein food. Modifications were made to increase the nutritional value by adding chicken liver and Moringa leaves and substituting them with Nutilor (Moringa Leaf Liver Nuggets). The research aims to analyze panelists' nutritional value and acceptability regarding the color, aroma, taste, and texture aspects of Nutilor products, as well as knowing market analysis and product prices. The method was an experiment conducted in the Food Laboratory, Nutrition Department, Poltekkes Kemenkes Tanjung Karang. Nutilor with chicken liver substitution, namely: F1 (14%), F2 (16%), F3 (18%), F4 (20%). Organoleptic testing using the hedonic test method (color, aroma, taste, texture, and overall acceptability) was conducted with 75 panelists and one replication. The most preferred Nutilor products are analyzed for their nutritional content, determining food costs and selling prices. Data were analyzed univariately using the Likert scale method. The organoleptic test results showed that the most preferred formula was F3 (90:25), with a nutritional value per serving (60 grams), namely E 171.2 kcal, P 9.1 g, L 8.2 g, KH 16.1, fiber 0.16, iron (Fe) 2.6 mg, the selling price per portion is IDR. 5000. The preferred product is F3, and based on the Likert scale, each formula has different colors and aromas. In further research, you need to pay attention to the time and temperature when frying and measure the amount of lemon used during marination.